Influence of some hydrophilic polymers on dissolution characteristics of furosemide through solid dispersion: An unsatisfied attempt for immediate release formulation (Journal of Pharmaceutical Negative Results, 2010)
Background: The objective of the present investigation was to enhance dissolutioncharacteristics of water insoluble drug, furosemide (FRMD), by solid dispersion invarious hydrophilic carriers. Materials and Methods: The solid dispersions wereprepared by solvent evaporation technique using urea and Hydroxy Propyl MethylCellulose (HPMC E50 LV). Physical mixtures of drug with above-mentioned polymerswere also prepared. Phase solubility studies were performed for drug in the presence ofexcipients in different ratios. The formulations were evaluated for drug content, in vitrodissolution, Fourier transform infrared (FT-IR) and differential scanning calorimetry(DSC). Similarity factor (f2) was calculated for comparison between dissolution ofpure drug and drug–polymer physical mixtures with solid dispersions. Results: Phasesolubility studies indicated linear increase in the drug solubility with increase in carrierconcentration. In vitro release studies revealed that dissolution characteristic of FRMDwas improved by solid dispersion technique. All the preparations of FRMD exhibitedsignificant improvement in its dissolution profiles. Solid dispersion of FRMD withHPMC E50 LV exhibited the highest rate and extent of dissolution. Optimizedbatches of solid dispersions of both the carriers were characterized by FT-IR and DSCanalysis, which indicated absence of major interactions between FRMD and carriers.Conclusion: Solid dispersion technique is one of the finest techniques to improvedissolution of poorly soluble drugs.